The Dominant Indicator in The Model of Strengthening the "Akhlak" Culture Through Servant Leadership: The Case of Indonesian State-Owned Enterprises (SOEs) - Arifin, Yusuf (Majalah Ilmiah Bijak, 2024)
Leadership and organizational culture are essential elements for the success of an organization, both business organizations and public organizations. In addition to knowing how close the relationship between Servant leadership and strengthening the AKHLAK culture is, this study aims to find dominant indicators that reflect the two variables. AKHLAK culture is a corporate culture based on the company's core values. The word AKHLAK is an acronym in Indonesian. The research sample involved 200 permanent employees in the West Java State Electricity Company (SEC)-Indonesia, which is one of the government-owned companies under Indonesian State-Owned Enterprises (SOEs), an "inclusion sample" of employees who have worked for at least five years. The study used quantitative methods with descriptive and verificative analysis approaches. The data analysis uses SEM-PLS (Structural Equation Modelling - Partial Least Squares). The results of the descriptive analysis in the study show that the implementation of servant leadership still plays a low role, and the AKHLAK culture is still not optimal. However, the verification analysis results show that Servant leadership's role strongly correlates with strengthening the AKHLAK culture.   Moreover, the dominant indicator for Servant leadership is the “Trush indicator, while the dominant indicator for AKHLAK culture is the “Loyalty indicator.